PENGENALAN SISTEM PERTANIAN TERPADU BERBASIS EKONOMI HIJAU GUNA MENDUKUNG MATA PELAJARAN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) DI SEKOLAH DASAR - Ayunis, Ayunis; Suhaemi, Zasmeli; Setiawan, Fadli; Putrananda, Hendri (LPPM Universitas Andalas, 2025)
Food availability in elementary schools plays a vital role in supporting local food security and fostering early environmental awareness. However, most schools in Indonesia have not yet utilized their yard areas optimally, and students’ understanding of sustainable agriculture remains limited. This community engagement program aimed to introduce an integrated farming model based on the green economy as a contextual learning medium and a support mechanism for implementing the Pancasila Student Profile Strengthening Project (P5). The program was conducted over four months at SDN 39 Tanjung Aur, Padang City, employing a school-based participatory approach. The activities consisted of three main stages: socialization, training, and mentoring with evaluation. A total of 24 students and 13 teachers participated actively in organic vegetable cultivation, compost production, and the maintenance of poultry as fertilizer producers. Evaluation was carried out through pre–posttests, observation, and the P5 rubric. The program demonstrated significant improvements in participants’ understanding and skills. Knowledge of integrated farming increased from 42% to 88%, and compost-making skills improved from 30% to 80%. Teachers successfully integrated the activities into thematic learning, while students showed higher levels of participation, independence, and environmental responsibility. The integrated farming model based on the green economy proved effective as a project-based learning strategy that enhances students’ competence while promoting food self-sufficiency in elementary schools. This program can be replicated in other schools as a best practice in green economy–based education.